Electrophilic ipso-Halocyclization of N-Phenyl-N-triflylpropiolamides Leading to 8-Halo-1-azaspiro[4.5]deca-3,6,9-trien-2-ones - Fiore, Vito A.; Keim, Michael; Werz, Roland; Maas, Gerhard (Synthesis, 2020)
N-Phenyl-N-triflylpropiolamides react with iodine chloride or iodine bromide by an intramolecular electrophilic ipso-halocyclization/nucleophilic halide addition sequence to furnish cyclohexadiene-spiro-γ-lactams. These products can undergo cleavage of the amide bond with primary amines and of the N–Cspiro bond with secondary amines, leading to N-alkyl-2-iodo-3-phenylacrylamides and N-(4-halophenyl)-2-iodo-3-(2-triflylamino)phenylacrylamides, respectively.
Keywords: electrophilic addition; propiolamides; γ-lactams; spiro compounds; triflylamides